Heterogeneous adverse childhood experiences and cognitive function in an elderly Chinese population: a cohort study - Ya Fang; Manqiong Yuan; Fengzhi Qin; Chuanhai Xu (BMJ Open)
Objective To identify the heterogeneity of adverse childhood experiences (ACEs) as well as their association with cognitive function in an elderly Chinese population.Design A retrospective cohort study.Participants The data were from the latest wave of the China Health and Retirement Longitudinal Study and a total of 7222 participants aged ≥60 were included.Primary and secondary outcome measures Latent class analysis was used to identify the classes characterised by 11 types of ACEs. Cognitive function was measured by the Mini-Mental State Examination (MMSE) and cognitive impairment was defined by education-specific threshold MMSE scores. Logistic models were constructed to examine the relationship between ACE classes and cognitive impairment. Several childhood and adulthood confounding factors were considered.Results Three ACE latent classes were identified. Of them, 76.09% were in the ‘Low ACEs’ class, 15.43% were in the ‘Household dysfunction’ class and 8.49% were in the ‘Child maltreatment’ class. The people in the ‘Low ACEs’ class seemed to have better childhood family financial situations and higher education levels. The population in the ‘Household dysfunction’ class tended to live in rural areas and have a higher proportion of men, whereas people in the ‘Child maltreatment’ class showed a significantly higher proportion of women and higher levels of chronic diseases. ‘Child maltreatment’ was related to a higher risk of cognitive impairment (OR=1.37, 95% CI: 1.12 to 1.68), while the risk of ‘Household dysfunction’ was not significantly different from that of the ‘Low ACEs’ participants (OR=1.06, 95% CI: 0.90 to 1.26).Conclusions The findings supported differences in cognitive function in elderly Chinese people exposed to different types of ACEs.